Versões do ponto de basta - Tatiana Pedrozo de Sousa Pinto (2022)
In this thesis, the concept of Quilting Point is presented as a stabilizer of discursive reality. The supported hypothesis is that this concept was never abandoned by Lacan and has a continuity in his work. Based on the assumption that the signifier only acquires meaning from its position in a chain, the signification always remains beyond, that is, with each addition of a new signifier, there is a retroactive modification of the meaning of the sentence. In view of this property, the need to create a Quilting Point was deduced, a concept conceived by Lacan in his third seminar, related 2) to that which does not deceive, an element of authority, with which there is no discussion, and which is erased from the field it organizes; 2) to the drive field: it’s linked to Bejahung: the libidinized representation introjected by the subject inaugurating the psychic function. As a word that forges a meeting point between signifier and signified and therefore sets the tone of the discourse, it is the Quilting Point that confers the internal coherence of discourse. Reflecting on the evolution of this concept implies considering what the subject can count on to anchor himself in the shifting field of the signifier. From a bibliographic review of the work of Lacan and commentators, it was possible to observe that Ponto de Basta is initially linked to the concept of ‘floating signifier’, ‘zero symbolic value’, present in Levi-Strauss theorization. It is also demonstrated, in this thesis, that these last two concepts were primordial for the creation of the lacanian idea of Name-of-the-Father, which had its statute modified from the moment it was perceived the impossibility of supposing the existence of a special signifier that would give stability to the field of the Other from outside. Thus, this special signifier came to be linked to the idea of an ‘extimity signifier’ (neologism created by Lacan), at the same time internal and external to the field of the Other due to its relationship with the real, the drive dimension. The ‘extimity signifier’ has a special character because it inaugurates the field of the signifiers – of the Other as a signifier’s treasure – as a consequence of the violent erasure of its correlative aspect to the real. The possible conclusion is that what is at the origin of the signifier is also related to what punctuates the chain, the ‘Quilting Point’. There is still a second consequence of this change, consistent with the evolution of Lacanian theorization, in which the emphasis shifts to the drive dimension. The thesis presents this theoretical shift in which it is underlined that for psychoanalysis what allows creating a padding point for the subject is the real of joy (jouissance).